Elderly women and mental health problems: A qualitative study in Kelantan, Malaysia - Ahmad Ramli, Fatimah Zailly (2013)
In the developing world, the disease burden of mental health problems of the aged is associated with demographic and economic change, education, urbanization, widowhood, war and displacement. In fact, data on non-organic disorders specifically among the aged in countries of the developing world are limited and varying in terms of type of mental illness.This situation is influenced by different cultural interpretations of psychiatric disorders.People ageing with mental illnesses present additional challenges which are not well understood. This includes the concern about their mental health status and the provision of geriatric services and facilities.These mental health problems among older adults suggest a need to understand the issues for individual and families in greater depth and to develop services and resources to support them.The paper will be discussed on how the caregivers conceptualised mental health problems and their perspectives on the trigger factors linked to mental illness among their older family members.Caregivers reported many different causes of mental illness.How they recognised the early signs of mental illness in older people and how they learned about the illness will be discussed further.Participants were recruited through a psychiatric hospital to ensure that a care recipient has a diagnosis of mental illness.Fourteen Malay caregivers of older people diagnosed with schizophrenia, depression and bipolar disorder were interviewed using semi-structured interviews. All interviews were fully transcribed into the Malay language before being translated into English.All transcriptions were analysed using a thematic analysis supported by the qualitative software (NVivo8).Identifiable themes and patterns of history, symptoms and diagnoses of illness among Malay older people with a mental health problem were reviewed to develop an overall story.Quotations from all participants are presented accordingly in the analysis to maintain rigor and trustworthiness